Biomechanical and tissue reaction: the effects of varying sutures size on canine abdominal wall stitching - Li, Shuai; Guo, Yizhe; Zhao, Xingkai; Lang, Dong; Zhou, Zhenlei (Frontiers in Veterinary Science, 2023)
Abstract Objective: Larger diameter sutures can provide sufficient tensile strength to surgical incisions but may exacerbate the inflammatory response caused by the amount of implanted foreign material. This experiment aims to investigate the differences in biomechanical stability and tissue reactivity after suturing canine midline abdominal incisions with different suture sizes. Method: Assessing the biomechanical differences between USP 2-0, 3-0, and 4-0 PGA sutures using uniaxial tensile testing on ex vivo canine midline skin and fascial muscle tissues using either a simple continuous or simple interrupted technique. mRNA and protein expression levels of inflammatory factors were measured through RT-PCR and ELISA. Tissue reactivity was evaluated using a semi-quantitative scoring system. Result: For strains below 30% in skin and below 50% in muscle, there were no significant differences among groups. The results of skin biomechanical testing showed that the USP 4-0 PGA suture group demonstrated significantly lower maximum tensile strength compared to the USP 2-0 PGA or USP 3-0 PGA suture groups. However, it remained capable of providing at least 56.3 N (1.03 MPa) tensile strength for canine skin incisions, matching the tensile strength requirements of general canine abdominal wall surgical incisions. In addition, there were no statistically significant differences observed in the maximum tensile strength among different size of sutures according to the data of biomechanical testing in muscle. Larger diameter sutures led to increased levels of inflammatory factors (IL-1β, IL-6, TNF-ɑ) and tissue reactivity. Simple interrupted sutures caused higher levels of inflammatory factors in muscular tissue compared to simple continuous sutures. Conclusion: USP 4-0 PGA sutures provide sufficient biomechanical stability for suturing canine abdominal skin and linea alba. Suture size significantly influences tissue reactivity after suturing, with smaller gauge sutures reducing early tissue inflammatory response. Thus, USP 4-0 PGA suture has more advantages to suturing canine abdominal surgical incisions.